Determinants of Food Security of Female and Male Headed Farming Households in Enugu State, Nigeria - Chiebonam Justina Ayogu; Chinasa Sylvia Onyenekwe; Ogechi Lynda Egwue; Favour Ezeh (Journal of Agricultural Extension, 2025)
This study examined the determinants of food security among female and male farming households in Enugu State. Specifically, it assessed the food security status by sex, identified the determinants and limitations of food security, and explored coping strategies. Using a multi-stage sampling approach, data were collected from 90 respondents via structured questionnaires. The analysis employed the Rasch model, ordered logit model, and mean. Results showed that male-headed households were more food secure than female-headed ones. Years of education were found to significantly (P<0.01) and positively (0.13) influence the food insecurity of male-headed households. Access to credit and extension services were found to significantly (P<0.01) and negatively (-1.25 and -2.26) influence the food insecurity of male-headed households. However, for female-headed households, none of the model variables showed statistically significant effects. The lack of farm machinery was found to be the most important limitation to food security ( X= 3.96), and the most popular coping strategy adopted is food rationing (X = 3.31). Policy recommendations include enhancing non-formal education through extension services, improving access to credit and infrastructure such as farm machinery.